BIOM-10. PREVALENCE OF NF1 MISSENSE MUTATIONS AND CANDIDATE MODIFIER GENES IN SPINAL NEUROFIBROMATOSIS PATIENTS. (9th November 2020) - Riva, Paola; Bianchessi, Donata; Mangano, Eleonora; Cesaretti, Claudia; Bettinaglio, Paola; Bordoni, Roberta; Tritto, Viviana; Battaglia, Cristina; Cagnoli, Giulia; Saletti, Veronica; Melone, Marina; Schettino, Carla; et al.
Abstract: INTRODUCTION: Spinal Neurofibromatosis (SNF), a distinct clinical entity of NF1, characterized by bilateral neurofibromas involving all spinal roots and a few, if any, cutaneous manifestations, entails greater morbidity than the classical form of disease. Nevertheless, there are no reliable patterns to sort out patients at risk for developing SNF. MATERIALS AND METHODS: We investigated 19 NF1 families with at least one SNF member, 37 sporadic SNF patient and 100 NF1 patients with classical form of disease. We applied Targeted NGS using a panel consisting of 139 genes encoding RAS pathway effectors, neurofibromin interactors and genes mapping at 17q11.2 region. RESULTS: In SNF patients we found a higher percentage of missense (21% versus 8%, p=0 0.016, OR 3.13 (95% CI 01.1 -8.2) and a lower percentage of nonsense NF1 mutations (12.5% versus 28%, , p= 0.026, OR 0.36 (95% CI 0.14–0.9) than in classical NF1 cases. Furthermore, we evaluated rare variants with damaging potential predictors in genes of the RAS pathway and in neurofibromin interactors. In more than one sporadic case possible pathogenic variants were found in LIMK2 (neurofibromin interactor), RASAL1, RASAL3, SOS1, A2ML1, MAP3K1 (RAS pathway effectors), while in more than one SNF family were detected RASAL1, RASAL3, MAP3K1 genes variations. CONCLUSIONS: Our results confirm the correlation between NF1 genotype and SNF phenotype as previously reported (Ruggieri, 2015), suggesting that neurofibromin gain-of-functions mutations are associated to SNF. In some patients, the co-occurrence of potential pathogenic variants in NF1 related genes with severe phenotypes was detected supporting their role as modifier genes and promising therapeutic targets.